UMP gets two animals to promote edu-tourism - Ong, Han Sean (The Star Publications (M) Berhad, 2017)
KUANTAN: Universiti Malaysia Pahang (UMP) has received two spotted deer (Axis axis) as part of an effort to position the university as an edu-tour centre.